GPS de precisión por el método estático relativo para puntos en aeropuertos (ING) - Roldán Rodríguez, Julio (2004)
Every country has its own geodetic reference frame, defined by a collection of specific parameters established by conventionals measurements. The differences in orientation, translations and scale with respect to a unique world system, defined as the International Reference Frame 2000 (ITRF00), brings consequences to aerial navigation when GPS is used because these differences generate planimetric errors on the order of ten meters and hundreds meters. Because of this, the need to establish standardization criteria for georeferening at the global level is foreseen, mainly when adopting as common reference for civil aviation the WGS84 and ITRF00. At present, the standardization for georeferening is not only done for civil aviation but for other fields such as geodesy, cartography and cadastre